Elucidating the impact of organic amendments on soil bacterial communities and strawberry yield in North Carolina - Adhikari, Tika B.; Philbrick, Ashley N.; Louws, Frank J. (Frontiers in Sustainable Food Systems, 2025)
Strawberry (Fragaria × ananassa Duchesne ex Rozier) is an important small fruit grown worldwide. Organic amendments can alter microbial communities and increase crop productivity. While research on organic amendments in strawberry cultivation has primarily focused on various regions in the U.S., especially the West Coast, there has been little to no investigation into their potential benefits in North Carolina (NC). A three-year trial was conducted from 2019 to 2022 at the Horticultural Crops Research Station in Castle Hayne, NC, U. S. A. The main objective of the study was to examine the effects of reduced rates of dried molasses (5.60 t/ha) and mustard meal (2.24 t/ha), a half-rate combination of both, a positive control (Pic Clor 60), and a negative control (no fumigated and no amended) on soil bacterial communities and strawberry yield. Our results from 16S microbiome amplicon sequencing showed significant variations in the composition of the soil bacterial community over time between the organic amendment treatments and the controls. The alpha diversity indices (Shannon index) of the soil bacterial microbiome were generally higher in plots with organic amendments than those treated with Pic Clor 60. Taxonomic classification revealed that the two phyla, Proteobacteria and Actinobacteriota, were prominent in the organic amendment treatments. The total marketable yield rankings for the three organic amendment treatments (dried molasses, mustard meal, and the half-rate combination of both) were comparable to those achieved through fumigation. The results indicated that bacterial structure and yield improved in the organic amendment plots, while microbial diversity decreased in the fumigation plots, and yields were lower in the untreated plots. This study will inform the selection of organic amendments to enhance microbial diversity and promote sustainability in strawberry farming in NC.